Feasibility Analysis of Four Tier Multiple Choice Diagnostic Test Instruments on Reaction Rate Material - huswatun hasanah; Abdullah Abdullah; R. Usman Rery (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2022)
This study aimed to analyze the feasibility of the four-tier multiple-choice diagnostic test instrument on the reaction rate material. The type of research used was development research referring to R&D (Research and Development) with a 4D development model. The 4D stage includes four stages: Define, Design, Develop, and Disseminate. The research subjects at the time of the small group trial were 20 students who had studied the reaction rate material. The data collection instrument used was a validation sheet. The data analysis technique was carried out through the calculations of validity, reliability, discriminatory power, and tier of the difficulty of the questions. The results showed that the four-tier multiple choice diagnostic test was feasible to identifying students' misconceptions with an average percentage of the content validity test of 96.97% with valid criteria, the value of the construction validity test was rcount > 0.444 with the category of all items valid, the score the reliability test was 0.83 (reliable) with very high criteria, the value of the discriminating power of the questions was 0.5 with good criteria, and the value of the difficulty tier of the questions was 0.5 with moderate criteria.